Inside the situation room : how a photograph showed America defeating Osama bin Laden - Elish, Dan (Compass Point Books, 2019)
Examines the events before, during, and after the killing of Osama bin Laden as shown through photographs of President Obama and his staff. Discusses the team of Navy SEALs who carried out the mission, and how the mission affected relations in the Middle East. Includes a glossary, sources for further information, discussion questions, and an index.